Enhancing Groundnut Productivity: Cluster Front Line Demonstration Approach in Kachchh District, Gujarat - Singh, Traloki; Dev, Rahul; Renjith, P. S.; Singh, Mohit; Anand, K. B. (International Journal of Bio-resource and Stress Management, 2024)
A field experiment was conducted during the kharif seasons (June to October) from 2019–2020 to 2021–2022 at farmers’ fields through ICAR-CAZRI Krishi Vigyan Kendra Kachchh-II to investigate the impact of cluster frontline demonstrations (CFLDs) on groundnut productivity and profitability. During the experiment period, a total of 75 CFLDs on Integrated Crop Management (ICM) in groundnut with the high-yielding variety Girnar-2 were undertaken in a 30-hectare area across 12 villages in the Bhuj, Nakhatrana, and Anjar talukas of Kachchh district. The improved variety Girnar-2 with a full package of practices was demonstrated in the plots, while existing technology was treated as the farmer’s practice (local check). Based on three years of data, the improved practice (IP) resulted in an average seed yield of 2215 kg ha-1, which was an increase of 20.08% compared to the farmer’s practice yield of 1826 kg ha-1. The demonstrated technology showed an average extension gap, technology gap, and technology index of 389 kg ha-1, 692 kg ha-1, and 23.80%, respectively. The economic analysis of the demonstrations revealed the viability of the enhanced technology, with a net return of 72,881 Rs. ha-1 and a benefit-cost ratio (BCR) of 3.01, compared to 57,691 Rs. ha-1 and a BCR of 2.67 for conventional technology. The results revealed that the adoption of the high-yielding variety with a full package of practices significantly increased groundnut productivity and reduced both extension and technology gaps.